2013
DOI: 10.1039/c3cc45588b
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of graphene quantum dots via size-selective precipitation and their application in upconversion-based DSSCs

Abstract: A novel approach to synthesize highly luminescent graphene quantum dots (GQDs) with well-defined sizes was explored based on simple oxidation of herringbone-type carbon nanofibers (HCNFs) and size-selective precipitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 26 publications
(3 reference statements)
2
73
0
Order By: Relevance
“…It is to be noted that in this work, the quantum dots were characterized without purification or isolation from the bulk suspension. It has been shown that quantum dots can be isolated by dialysis (Pan et al 2010), reverse phase high performance liquid chromatography (Tang et al 2012), or sizeselective precipitation (Lee et al 2013). However, we believe that the bulk suspension consists of mostly quantum dots and any relatively larger sheets are still nanometer-sized grains.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is to be noted that in this work, the quantum dots were characterized without purification or isolation from the bulk suspension. It has been shown that quantum dots can be isolated by dialysis (Pan et al 2010), reverse phase high performance liquid chromatography (Tang et al 2012), or sizeselective precipitation (Lee et al 2013). However, we believe that the bulk suspension consists of mostly quantum dots and any relatively larger sheets are still nanometer-sized grains.…”
Section: Resultsmentioning
confidence: 99%
“…In this method, graphite flakes were sonicated in H 2 SO 4 and HNO 3 (acid oxidation) followed by washing and autoclave. Lee et al (2013) prepared GQD based on the oxidation of herringbonetype carbon nanofibers and size-selective precipitation. Other routes that use the bottom up approach of graphene quantum dots include microwave-assisted hydrothermal technique using sugar as the starting material (Tang et al 2012), electrochemical approach using graphite electrode (Li et al 2011), or complex solution chemistry (Yan et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2b shows high-resolution TEM images of the CGQDs, which demonstrates that the GQDs are highly crystalline with lattice spacing of 0.24 AE 0.02 nm associated with hexagonal lattice fringes of graphene derivatives. [6] The Fast Fourier Transform (FFT) pattern clearly shows the hexagonal pattern of the graphene structure associated with the [001] plane, as shown in Figure 2b (inset i). A single layer of graphene shows six carbon atoms in hexagonal pattern in TEM images.…”
Section: Selective Liquid-phase Extraction Of Carboxylate-rich Graphementioning
confidence: 99%
“…[6] It is noteworthy that GQDs possess more organic molecule-like structure with chemically activated oxygen-rich characteristics such as carboxylic acid (-COOH), [7] which enable GQDs to modify their chemical and optical functionalities using hybridizing other organic or inorganic single molecules. [8] Thus, the engineering by the chemical functionalities on their surface or edge-sites consequently offers many advantages in controlling the electronical and optical properties of GQDs for intended applications.…”
Section: Selective Liquid-phase Extraction Of Carboxylate-rich Graphementioning
confidence: 99%
“…Generally, the approaches can be divided into two groups: top-down and bottom-up methods. In the top-down methods, GQDs are usually synthesized through the cleavage of relatively large bulk precursors, such as graphite [53][54][55], carbon black [56][57][58], coal [59][60][61], metal-organic framework (MOF) [40], 3D graphene [62], graphene oxide (GO) [63][64][65][66][67], carbon nanotubes [68][69][70], carbon fiber [53,[71][72][73] and C 60 [74,75] into small pieces of graphene sheets by chemical oxidation etching [76][77][78][79][80][81], electrochemical exfoliation [65,[82][83][84][85], Li/K intercalation [86,87], hydrothermal/solvothermal treatment [88][89][90][91][92][93][94], microwave irradiation [95...…”
Section: Synthesis and Optical Property Of Gqdsmentioning
confidence: 99%